Stromal protein CCN family contributes to the poor prognosis in lower-grade gioma by modulating immunity, matrix, stemness, and metabolism - Liu, Zhihui; Wu, Jiasheng; Ji, Hang; Zhao, Hongtao; Wang, Fang; Dong, Jiawei; Zhang, Jiheng; Wang, Nan; Yan, Xiuwei; Wang, Kaikai; Hu, Shaoshan (Frontiers in Molecular Biosciences, 2022)
Background: The CCN family of stromal proteins is involved in the regulation of many important biological functions. However, the role of dysregulated CCN proteins in LGG has not been adequately studied. Methods: We verified the clinical significance of the CCN proteins by RNA-seq data from multiple cohorts. Next, we constructed CCNScore using LASSO-regression analysis. And we used the PanCanAtlas data to explore the multiple biological functions of CCN family in LGG. Finally, through the MEXPRESS database, we overviewed the gene mutations, copy number variants, methylation details and promoter changes of CCNs in LGG. Results: We found that CCN family especially CCN4 was related to poor prognosis in LGG, next we created the CCNScore (CCN1=0.06, CCN4=0.86), which was critical for prognosis forecast, subtype assessment and therapy selection. We found that High-CCNScore group possessed a glioblastoma-like mutational mode with EGFRmut, PTENmut and NF1mut, including mainly classic-like and mesenchymal-like subtypes, with hypo-methylation levels, containing MES, NPC and OPC-like glioma stem cell (GSC), with higher stemness, higher inflammation, higher extracellular matrix and multiple metabolic dysfunction. In contrast, the Low-CCNScore group consisted mainly of IDH-mut LGG, characterized by IDH1, TP53, CIC and ATRX mutations, with hyper-methylation status, with GSC restriction, associated with high differentiation, low proliferation, immune quietness and low extracellular matrix stiffness. Conclusion: In summary, our bioinformatics mining outlined the CCN family in LGG and provided a novel and critical target for LGG.